Molecular Insights of Dengue Virus and its Effects on Different Ecological Regions of Pakistan - Zaynab, Madiha (International Journal of Molecular Microbiology, 2019)
Dengue virus (DENV) is a mosquito-transmitted RNA virus affecting human populations, causing significant economic and social impact. Computational approaches have elucidated on dengue’s population dynamics with the aim to provide not only a better understanding of the evolution and epidemiology of the virus but also robust intervention strategies. Over the past decade, dengue infection has expanded over the vast geographical range. This may be caused by more frequent international travel, climate change, virus evolution, unplanned urbanization, globalization, population mobility and failure of Aedes mosquitoes control. Here, we review recent advances in our understanding of the biology of DENV and describe its effects in the ecological region of Pakistan.